2004
DOI: 10.3354/ame036247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prey abundance and light intensity on nutrition of a mixotrophic flagellate and its competitive relationship with an obligate heterotroph

Abstract: The mixotroph Poterioochromonas malhamensis was grown in batch and semicontinuous cultures in order to examine the dependence of phagotrophy versus phototrophy at bacterial densities similar to those found in oligo-and mesotrophic lakes in combination with differing light regimes. In addition, the growth rates and biomass accumulation of the mixotroph were compared to those of the heterotroph Spumella elongata grown under similar conditions. In P. malhamensis, primary production rates and cell-specific chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…We used the conversion factor from Wetzel & Likens (1991) as this factor has been applied by other investigators working on P. malhamensis (e.g. Pålsson & Daniel 2004) and closely matches recently suggested carbon conversion factors (e.g. Menden-Deuer & Lessard 2000).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the conversion factor from Wetzel & Likens (1991) as this factor has been applied by other investigators working on P. malhamensis (e.g. Pålsson & Daniel 2004) and closely matches recently suggested carbon conversion factors (e.g. Menden-Deuer & Lessard 2000).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in the case of Poterioochromonas malhamensis this argument was used in regard to Type Strain 933/1a (e.g. Holen 1999, Pålsson & Daniel 2004), but careful re-evaluation of the data showed that the findings on the different strains used in the laboratory studies were not contradictory at all (see subsection on the contribution of phototrophy; see also Pringsheim 1952) and that only the interpretation of the results differed. In effect, even a 60 yr old laboratory strain still responds in the same way as recently isolated strains.…”
Section: Current Limitations In Laboratory Studies Of Bacterivorous Fmentioning
confidence: 99%
See 1 more Smart Citation
“…This success is due to the versatility of their behaviour: phagotrophy allows predominantly phototrophic mixotrophs to gain limiting nutrients in both laboratory (Nyagaard & Tobiesen 1993) and field conditions (Stoecker et al 1997, Olrik 1998, whereas mixotrophs that are mainly heterotrophic can survive in low prey environments by increasing their chlorophyll content (Sanders et al 1989). In lakes with low bacterial abundances, the ability of MxFl to photosynthesize enables them to dominate over heterotrophs in terms of biomass (Palsson & Daniel 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the light level provided in our L treatments was low, phototrophic growth of mixotrophic flagellates and ciliates probably contributed to higher protozoan biomass in the L treatments. At a similar light intensity, Pålsson & Daniel (2004) observed that photosynthesis by the widely occurring flagellated mixotroph Poterioochromonas malhamensis could support 80% of the gain in cell carbon when bacterial abundances were low. Nevertheless, higher flagellate biomass in the L treatments may also partly be a result of ingestion of bacteria growing in the presence of both 'old' and algal-derived DOM.…”
Section: Protozoamentioning
confidence: 76%